DYNAMIC BEHAVIOR OF FLOOR SLAB WITH STIFFENER BEAM DUE TO BLAST LOAD FROM MODIFICATION OF REED EQUATION - Haryo Koco Buwono (International Journal of Civil Engineering and Infrastructure, 2021)
Explosions in buildings are not always the result of terrorist attacks, but can also be caused by several work accidents due to explosive tools or materials as trigger of problems in construction. Friedlander's equation has many modifications including the Reed equation. Reed proposes a modification of Friedlander equation using 4th order polynomial. The Reed equation is still not close relatively to the Friedlander equation. The Reed equation is only calculated up to t = 25/7 (s) in the negative phase. Meanwhile, the Friedlander is calculated at t = 5 if both are reviewed at no load or one unit condition. It is necessary to evaluate using the 4th order polynomial equation which is close to the Friedlander explosion equation. Dynamic behavior of structures must be considered in the design of structural elements. The purpose of this study is to analyze numerically the effect of explosions on orthotropic slabs which have partial fixity placement and stiffeners in the x direction, namely in the short span direction. The behavior of the plate orthotropic configuration, the localized blast load are centered in the middle of the strain, and the effect of thickness and stiffening on the vertical deflection of the plates are solved numerically using two auxiliary equations in the x and y-directions. From the analysis, it is found that there is vertical deflection with related to time. This paper introduces the dynamic behavior of Reed's modified blast loads with 4th order polynomial on orthotropic plates with x-direction stiffener beam.